Institutional inertia and climate change: a review of the new institutionalist literature. (29th May 2014) - Munck af Rosenschöld, Johan; Rozema, Jaap G.; Frye‐Levine, Laura Alex
Abstract : Climate scientists and policy analysts alike have repeatedly called for urgent mitigating action to avoid the most adverse effects of climate change. However, within the political arena this action is largely lacking. To understand this discrepancy, we consider the institutions in climate change policy to be of central importance. Renewed interest in institutions has been generated to a great extent by 'new institutionalism', a field of research combining economics, political science, and sociology, and which has become increasingly popular since the 1980s. The tendency of institutions to resist change and thereby stabilize policy can be understood by using the concept of institutional inertia. Our review of the new institutionalist literature on climate change identifies five main mechanisms that generate institutional inertia: costs, uncertainty, path dependence, power, and legitimacy. Means of addressing these mechanisms are proposed by referring to the literature on institutional entrepreneurship and institutional work. A focus on the mechanisms that generate and regenerate institutional inertia is beneficial for future research on institutions and climate change, as it can be used to study bottlenecks for action and address more clearly the urgency of necessary policy interventions. WIREs Clim Change 2014, 5:639–648. doi: 10.1002/wcc.292 This article is categorized under: Climate Economics > Iterative Risk‐Management Policy Portfolios Policy and Governance > Multilevel and Transnational Climate Change Governance